New generation washable PES membrane face mask for virus filtration - Talukder, Md Eman; Alam, Fariya; Pervez, Md. Nahid; Jiangming, Wang; Hassan, Fahim; Stylios, George K.; Naddeo, Vincenzo; Song, Hongchen (Nanocomposites, 2022)
Membrane materials might be used for face protection because they can decontaminate the inhaled air from particle pollution and viruses like the SARS-Cov0-2 which damages our respiration system. In this study, plyethersulfone membranes (PES) were synthesized with green solvent at room temperature and its filtration effectiveness was investigated against nano-bacteria (size 0.05 to 0.2 µm) by measuring their Bacterial Filtration Efficiency (BFE) and micro aerosol size (0.3 µm), and Particulate Filtration Efficiency (PFE). The average SARS-CoV-2 diameters are between 50 nm to 160 nm. A series of experiments were performed to accomplish between 0.03 to 0.21 µm PES sponge like diameters so that can be used for SARS-CoV-2 filtration. Results showed that nanofiltration/ultrafiltration could filter 99.9% of bacteria and aerosol from contaminated air the size of the Covid-19 molecule.